The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1073/pnas.0900833106
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid change converts Aurora-A into Aurora-B-like kinase in terms of partner specificity and cellular function

Abstract: Aurora kinase-A and -B are key regulators of the cell cycle and tumorigenesis. It has remained a mystery why these 2 Aurora kinases, although highly similar in protein sequence and structure, are distinct in subcellular localization and function. Here, we report the striking finding that a single amino acid residue is responsible for these differences. We replaced the Gly-198 of Aurora-A with the equivalent residue Asn-142 of Aurora-B and found that in HeLa cells, Aurora-A G198N was recruited to the inner cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 45 publications
7
84
0
Order By: Relevance
“…Specifically, AurA (G198N) was capable of compensating for the loss of AurB function by forming a complex with INCENP and Survivin and localizing to the inner centromere and the spindle midzone in a manner dependent on its interaction with the components of the CPC. [49][50][51][52] Taken together, these data suggest that the different spatio-temporal distribution and biological functions of AurA and AurB are primarily determined by the nature of their interacting cofactors. If so, can such cofactors, while targeting AurA and AurB to different cellular compartments, still use similar strategies to regulate the kinase activity?…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 81%
“…Specifically, AurA (G198N) was capable of compensating for the loss of AurB function by forming a complex with INCENP and Survivin and localizing to the inner centromere and the spindle midzone in a manner dependent on its interaction with the components of the CPC. [49][50][51][52] Taken together, these data suggest that the different spatio-temporal distribution and biological functions of AurA and AurB are primarily determined by the nature of their interacting cofactors. If so, can such cofactors, while targeting AurA and AurB to different cellular compartments, still use similar strategies to regulate the kinase activity?…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 81%
“…Recently, Fu et al (Fu et al, 2009) and Hans et al (Hans et al, 2009) showed that a single amino acid change within the Aurora-A kinase domain (Gly198 to the equivalent Asn residue of Aurora-B) is sufficient to convert it into an Aurora-B-like kinase in HeLa cells. The equivalent residue in ApAurora (supplementary material Fig.…”
Section: Ancestral Aurora For Vertebrate Aurorasmentioning
confidence: 99%
“…Aurora kinases exert multiple roles in diverse cell cycle-related processes by phosphorylating a wide variety of substrates (Biggins and Murray, 2001;Carmena et al, 2009;Fu et al, 2009;Hans et al, 2009;Van Damme et al, 2011;Petrovská et al, 2012;Hochegger et al, 2013;Demidov et al, 2014;Goldenson and Crispino, 2015;Weimer et al, 2015). However, to date, only histone H3 (Hsu et al, 2000) and TPX2 have been reported as alpha Aurora substrates in plants (Demidov et al, 2005;Tomaštíková et al, 2015).…”
Section: Discussionmentioning
confidence: 99%